1967
DOI: 10.1111/j.1440-6055.1967.tb02123.x
|View full text |Cite
|
Sign up to set email alerts
|

The Arthropoda of Australian Caves

Abstract: The Arthropoda of Australian Caves are reviewed and assigned to four ecological categories: trogloxenes, first and second level troglophiles, and troglobites. It is shown that Australia has few troglobitic species and this supports an earlier suggestion that extensive secondary extinction of cavernicoles occurred during the Pleistocene and Recent epochs as a result of climatic change. It is further suggested that flooding of Australian caves during the Pleistocene followed by dehydration through general change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…Western Australia has been considered to have poor prospects for supporting subterranean faunas, owing to the lack of water and low nutrient input from xeric plant communities (Moore 1964;Hamilton-Smith 1967;Barr 1973;Howarth 1980). Knowledge of this region, however, has developed substantially in the last decade, such that it is now recognized to include one of the world's most diverse and notable subterranean faunas (Holthuis 1960;Humphreys 1992, 1998;Wilson and Ponder 1992;Bartsch 1993;Humphreys 1993aHumphreys , 1993bHumphreys , 1993cHumphreys , 2000Humphreys , 2001; Bruce and Humphreys, 1993;Harvey et al 1993;Aubrecht and Kozur 1995;Baltanas and Danielopol 1995;Yager and Humphreys 1996;Bradbury and Williams 1996a, 1997a, 1997bHarvey 1998;Knott and Halse 1999;Bradbury 2000Bradbury , 2002Watts and Humphreys 2000, 2001, 2003Moore et al 2001;Marrnonier 2002, 2003).…”
Section: Introduction Until Relatively Recently the Groundwater Fauna Ofmentioning
confidence: 99%
“…Western Australia has been considered to have poor prospects for supporting subterranean faunas, owing to the lack of water and low nutrient input from xeric plant communities (Moore 1964;Hamilton-Smith 1967;Barr 1973;Howarth 1980). Knowledge of this region, however, has developed substantially in the last decade, such that it is now recognized to include one of the world's most diverse and notable subterranean faunas (Holthuis 1960;Humphreys 1992, 1998;Wilson and Ponder 1992;Bartsch 1993;Humphreys 1993aHumphreys , 1993bHumphreys , 1993cHumphreys , 2000Humphreys , 2001; Bruce and Humphreys, 1993;Harvey et al 1993;Aubrecht and Kozur 1995;Baltanas and Danielopol 1995;Yager and Humphreys 1996;Bradbury and Williams 1996a, 1997a, 1997bHarvey 1998;Knott and Halse 1999;Bradbury 2000Bradbury , 2002Watts and Humphreys 2000, 2001, 2003Moore et al 2001;Marrnonier 2002, 2003).…”
Section: Introduction Until Relatively Recently the Groundwater Fauna Ofmentioning
confidence: 99%
“…Considered depauperate of karstic habitat and having widespread aridity, historically, Australia was considered a poor prospect for subterranean fauna. Australia's arid Pleistocene climatic history was deemed to lack key climate history events, such as Pleistocene glaciations (Moore 1964;Hamilton-Smith 1967;Barr 1973), which were considered drivers of subterranean biodiversity in the northern hemisphere (Peck 1980;Boutin 1994). This excludes Tasmania (Derbyshire 1972), which is richly endowed with karst and caves and was subject to Pleistocene glaciations.…”
Section: Introductionmentioning
confidence: 99%
“…Many terrestrial obligates found in earlier New South Wales surveys (particularly the spiders and insects) display little or no adaptation. This prompted Hamilton-Smith (1967, 1971 to introduce the term second-level troglophile to distinguish "those forms living out their total life-cycle within caves, known only from caves, but not exhibiting any modification to the cave environment" (Hamilton- Smith, 1971: 64). Use of this term detracts from the fact that these forms are an important component of the obligate fauna, so we do not distinguish between troglobites and second-level troglophiles in this paper.…”
Section: Obligate Faunasmentioning
confidence: 99%
“…This paper focuses on the issue of subterranean biodiversity in another region of Australia, namely the karsts of New South Wales and the Australian Capital Territory (hereafter included with New South Wales). Hamilton-Smith (1967) compiled the first systematic review of the total Australian cavemicolous fauna and found that the karsts of New South Wales had a comparatively richer fauna than elsewhere on the continent. Gray's (1973) subsequent review of the Australian cave spider fauna added further to the tally provided by Hamilton-Smith.…”
Section: Introductionmentioning
confidence: 99%